Evaluation of Safety and Protective Efficacy of a waaJ and spiC Double Deletion Korean Epidemic Strain of Salmonella enterica Serovar Gallinarum - Zhang, Jun-Feng; Shang, Ke; Wei, Bai; Lee, Yea-Jin; Park, Jong-Yeol; Jang, Hyung-Kwan; Cha, Se-Yeoun; Kang, Min (Frontiers in Veterinary Science, 2021)
With an aim to develop a highly attenuated and strongly immunogenic differentiation of infected and vaccinated animals (DIVA) vaccine candidate, a waaJ (a gene involved in the synthesis of lipopolysaccharide) and spiC (a virulence gene) double deletion Korean epidemic strain of S. enterica ser. Gallinarum (SG005) was constructed. Our results showed that the growth and biochemical characteristics were not altered by this double deletion. The double deletion strain contained dual markers. One was a bacteriological marker (rough phenotype) and the other was a serological marker (DIVA). The double deletion strain showed good genetic stability and reduced resistance to environmental stresses in vitro; furthermore, it was extremely safe and highly avirulent in broilers. Single intramuscular or oral immunization of 7-day-old broilers with the double deletion strain could stimulate the body to produce antibody levels similar to the conventional vaccine strain SG9R. In addition, against a lethal wild-type challenge, it conferred effective protection that was comparable to that seen in the group vaccinated with SG9R. In conclusion, this double deletion strain may be an effective vaccine candidate for controlling S. enterica ser. Gallinarum infection in broilers.